Pengaruh Model Pembelajaran Kooperatif Tipe The Power Of Two Terhadap Hasil Belajar Matematika Siswa SMP Negeri 3 Mataram - Nunung Rusdiyawanti; Nurul Hikmah; Syahrul Azmi; Laila Hayati (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This study aims to determine the influence of cooperative learning method type of the power of two on mathematics learning achievement of VIII grade students of SMP Negeri 3 Mataram academic year 2019/2020. This study used quasy experimental design. Population in this study consist all of VIII grade student from 7 class and 2 class as sample by using Cluster random sampling.The data collecting technique is using essay. Data analysis technique using t test to determine the influenceof the power of two cooperative learning method on mathematics learning achievement of VIII grade students of SMP Negeri 3 Mataram academic year 2019/2020. For the experimental class it is applied using the cooperative learning model type the power of two and for the control class it is applied using the direct learning model. Based on data analysis, mathematics learning achievement student that used cooperative learning method type of the power of two is higher than students that used conventional learning method. This indicates that there is an influence of the type the power of two cooperative learning methodon mathematics learning achievement of VIII grade students of SMP Negeri 3 Mataram academic year 2019/2020.